DOI: 10.1007/978-3-211-09469-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation and brain injury after intracerebral hemorrhage

Abstract: SummaryMicroglial activation and thrombin formation contribute to brain injury after intracerebral hemorrhage (ICH). Tumor necrosis factor-alpha (TNF-) and interleukin-1 beta (IL-1) are 2 major proinflammatory cytokines. In this study, we investigated whether thrombin stimulates TNF-and IL-1 secretion in vitro, and whether microglial inhibition reduces ICH-induced brain injury in vivo.There were 2 parts to this study. In the first part, cultured rat microglial cells were treated with vehicle, thrombin (5 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…6 Thrombin also stimulates microglia to secrete IL-1b, resulting in similar damaging effects as TNF-α, such as neurotoxicity, opening of the BBB, and induction of apoptosis. 142 The role of this mechanism in ICH-mediated injury is supported by studies showing attenuation of brain edema by the overexpression of IL-1b receptor antagonists.…”
Section: 142mentioning
confidence: 99%
“…6 Thrombin also stimulates microglia to secrete IL-1b, resulting in similar damaging effects as TNF-α, such as neurotoxicity, opening of the BBB, and induction of apoptosis. 142 The role of this mechanism in ICH-mediated injury is supported by studies showing attenuation of brain edema by the overexpression of IL-1b receptor antagonists.…”
Section: 142mentioning
confidence: 99%
“…Microglia, the resident immune cells of the central nervous system (CNS; Gehrmann et al 1995), play a central role in the CNS inflammatory response to an injury (Koshinaga et al 2000;Wu et al 2008;Jin et al 2010). The modulation of microglial activation has been shown to exert protective properties (Bye et al 2007;Liu et al 2010;Wilms et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β has been related to oedema formation in ICH (Wagner et al, 2006;Wagner and Dwyer, 2004), inflammation, as well as apoptosis and vasogenic oedema in several brain pathologies (Holmin and Mathiesen, 2000) and central nervous system injury (Allan and Rothwell, 2003). Wagner et al (2006) report upregulation of IL-1β gene expression the first hours after haematoma induction in ICH, while Wu et al (2008) showed that IL-1β levels were increased after thrombin treatment in the culture medium. A reduction of IL-1β has been observed after administration of Curmucin (King et al, 2011) or deferoxamine (Miao et al, 2012), in mice and rat models of ICH respectively, with final reduced neurological deficiency.…”
Section: Discussionmentioning
confidence: 99%